Evaluation of taurodontism in panoramic radiographies in a Peruvian population - Alvarez Acevedo, Brenda Silvana (2022)
Taurodontism is a dental anomaly, so it has clinical implications in different areas of dentistry. Objective: To evaluate taurodontism in panoramic radiographs in a Peruvian population. Material and Methods: 220 digital panoramic radiographs were evaluated in which the type of taurodontism was classified in permanent first molars according to the Shifman and Chanannel method. Observations were recorded on a data sheet. Results: 51% belonged to males and 49% to females. The frequency of taurodontism, according to sex, was higher in men in 24%, and in women it was 20%. The most frequent type of taurodontism was hypotaurodontism in 80%. The most frequent location and first molar was the upper jaw with 68% and the upper left molar with 37%, respectively. Conclusion: The evaluation of taurodontism in digital panoramic radiographs was characterized by being more frequent in men, in terms of type and location, hypotaurodontism and maxilla, respectively, were more frequent. Furthermore, it was characterized by being more frequent in the upper first molars on the left side.